Adoption of Model Nutrition Garden by Farming Families of Punjab (Indian Journal of Extension Education, 2017)
The present investigation was conducted to study the extent of adoption of model nutrition garden by selected farming families of Punjab. Ten districts were randomly selected with the help of respective KVKs. From each district, one village was purposively selected. Twenty farmers were randomly selected from each village. The study highlighted that large proportion of the respondents (73.2 %) used one kanal land for nutrition garden and nearly forty per cent respondents (47%) cultivated vegetables, pulses and fruits in their nutrition garden. Adoption quotient of land used for nutrition garden was 43 and adoption quotient of crops (vegetables, pulses and fruits) cultivated in nutrition garden was 80. The whole adoption of model nutrition garden was 61.5 per cent. The findings revealed that technological gap for practice I (area under nutrition garden) was 56.3 per cent and for practice II (crops cultivated in nutrition garden) was 19.6 per cent.